Efficacy of an Internet-Based Learning Module and Small-Group Debriefing on Trainees' Attitudes and Communication Skills Toward Patients With Substance Use Disorders. (March 2015) - Lanken, Paul N.; Novack, Dennis H.; Daetwyler, Christof; Gallop, Robert; Landis, J. Richard; Lapin, Jennifer; Subramaniam, Geetha A.; Schindler, Barbara A.
<x xml:space="preserve">Abstract</x> Purpose To examine whether an Internet-based learning module and small-group debriefing can improve medical trainees' attitudes and communication skills toward patients with substance use disorders (SUDs). Method In 2011–2012, 129 internal and family medicine residents and 370 medical students at two medical schools participated in a cluster randomized controlled trial, which assessed the effect of adding a two-part intervention to the SUDs curricula. The intervention included a self-directed, media-rich Internet-based learning module and a small-group, faculty-led debriefing. Primary study outcomes were changes in self-assessed attitudes in the intervention group (I-group) compared with those in the control group (C-group) (i.e., a difference of differences). For residents, the authors used real-time, Web-based interviews of standardized patients to assess changes in communication skills. Statistical analyses, conducted separately for residents and students, included hierarchical linear modeling, adjusted for site, participant type, cluster, and individual scores at baseline. Results The authors found no significant differences between the I- and C-groups in attitudes for residents or students at baseline. Compared with those in the C-group, residents, but not students, in the I-group had more positive attitudes toward treatment efficacy and self-efficacy at follow-up (P < .006). Likewise, compared with residents in the C-group, residents in the I-group received higher scores on screening and counseling skills during the standardized patient interview at follow-up (P = .0009). Conclusions This intervention produced improved attitudes and communication skills toward patients with SUDs among residents. Enhanced attitudes and skills may result in improved care for these patients.